2016
DOI: 10.1071/cp15029
|View full text |Cite
|
Sign up to set email alerts
|

Mapping spatial variability of leaf nutrient status of oil palm (Elaeis guineensis Jacq.) plantations in India

Abstract: Spatial variability of leaf nutrients in oil palm (Elaeis guineensis Jacq.) plantations in Goa, Karnataka, Mizoram and Gujarat states of India were examined for implementation of site-specific fertilisation programs. Georeferenced leaf samples were collected randomly for the oil palm plantations. The leaf nutrient concentrations were assessed and analysed statistically and geostatistically. The concentrations of leaf nutrients such as nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The values of N, K, S, B, P, Mg, Zn, Mn, and Fe showed high spatial dependence according to classes set by Dalchiavon & Carvalho (2012), indicating that leaf nutrient contents are not randomly distributed (Table 2). These results agree with those reported by Behera et al (2016), Lima et al (2016), and Gazola et al (2017), who also found spatial dependence of leaf nutrient contents in oil palm, papaya, and soybeans, respectively. From the spatial dependence, it was possible to obtain maps for individual definition of the spatial variability of the nutrients.…”
Section: Spatial Variability Of Leaf Nutrient Contentsupporting
confidence: 93%
“…The values of N, K, S, B, P, Mg, Zn, Mn, and Fe showed high spatial dependence according to classes set by Dalchiavon & Carvalho (2012), indicating that leaf nutrient contents are not randomly distributed (Table 2). These results agree with those reported by Behera et al (2016), Lima et al (2016), and Gazola et al (2017), who also found spatial dependence of leaf nutrient contents in oil palm, papaya, and soybeans, respectively. From the spatial dependence, it was possible to obtain maps for individual definition of the spatial variability of the nutrients.…”
Section: Spatial Variability Of Leaf Nutrient Contentsupporting
confidence: 93%
“…This means that they did not show spatial dependence. However, spatial dependence was found for leaf Mg content both by Behera et al (2016) in an oil palm field in India and by Qamar Uz and Schumann (2006) in a citrus field in the USA. In addition, López-Granados et al (2004) found spatial dependence of leaf N content in an olive field in Spain.…”
Section: -Geostatistics Analysismentioning
confidence: 95%
“…López-Granados et al ( 2004) and Behera et al (2016) verified the necessity of determining spatial variability in nutrient status before planning a differential fertilizer program. López-Granados et al ( 2004) used contour maps of leaf nutrients, achieved by kriging, to estimate the percentage of an olive orchard in Spain that needed fertilization, where the concentration of the respective nutrients did not exceed the fertilization threshold.…”
Section: -Geostatistics Analysismentioning
confidence: 97%
See 2 more Smart Citations